Reduction of GHG and nitrogen emissions from dairy production systems - Amon, Barbara (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This presentation was given by Dr. Barbara Amon at the kick-off meeting on "Piloting and scaling of low emission development options in large scale dairy farms in China" on September 28, 2020.